ANALISIS PENGARUH PROFITABILITAS DAN FINANCIAL LAVERAGE TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia) (Students' Journal of Accounting and Banking, 2014)
This study aims to identify and analyze the influence of ROA, NPM, OPM DER, and DR to the stock price on the Food and Beverage companies listed in Indonesia Stock Exchange. The population in this study are all Food and Beverage company whose shares are listed on the Indonesia Stock Exchange (IDX) during the period from 2008 to 2012 as many as 17 companies. While the sample is the entire Food and Beverage company whose shares are listed on the Indonesia Stock Exchange (IDX) during the period from 2008 to 2012 as many as 11 companies. The sampling technique used was purposive sampling. Analysis tools, we choose in this study is multiple linear regression. Based on the partial hypothesis testing, indicating the influence of ROA on stock prices is significant. In the second hypothesis testing between NPM influence on stock prices is not significant. In the third hypothesis testing between OPM influence on stock prices is not significant. In the fourth hypothesis between DER influence on stock prices is not significantly negative. In the fifth hypothesis testing between DR influence on stock prices is not significant. Based on simultaneous hypothesis testing, a significant difference between the variables NPM, ROA, DER, OPM and DR together - equal to the stock price.Keywords: NPM, ROA, DER, OPM, DR and stock price